1988
DOI: 10.1111/j.1476-5381.1988.tb11576.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective regulation of β1‐and β2‐adrenoceptors in the human heart by chronic β‐adrenoceptor antagonist treatment

Abstract: In 44 patients undergoing coronary artery bypass grafting, the effect of chronic administration of the fi-adrenoceptor antagonists sotalol, propranolol, pindolol, metoprolol and atenolol on fiadrenoceptor density in right atria (containing 70% PB-and 30% P2-adrenoceptors) and in lymphocytes (having only f2-adrenoceptors) was studied.2 fl-Adrenoceptor density in right atrial membranes and in intact lymphocytes was assessed by (-)[1225I]-iodocyanopindolol (ICYP) binding; the relative amount of right atrial P,-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
2
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(44 citation statements)
references
References 32 publications
(38 reference statements)
1
40
2
1
Order By: Relevance
“…It has been shown in a variety of recombinant systems that long-term treatment with inverse agonists causes much larger increases in receptor density than do "neutral" antagonists (Milligan and Bond 1997). Thus, because the "second generation" β-1 AR blockers bisoprolol and metoprolol have been shown the exert considerable inverse agonism activity (Maack et al 2001), it might well be that the increase in β-AR density observed in human heart during longterm treatment with these β-1 AR blockers Gilbert et al 1996;Heilbrunn et al 1989;Michel et al 1988;Sigmund et al 1996;Waagstein et al 1989) is due to their inverse agonism activity. In this context, it is interesting to note that also carvedilol has been found to exert (weak) inverse agonism (Maack et al 2000), but as discussed earlier it did not increase cardiac β-AR density in CHF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown in a variety of recombinant systems that long-term treatment with inverse agonists causes much larger increases in receptor density than do "neutral" antagonists (Milligan and Bond 1997). Thus, because the "second generation" β-1 AR blockers bisoprolol and metoprolol have been shown the exert considerable inverse agonism activity (Maack et al 2001), it might well be that the increase in β-AR density observed in human heart during longterm treatment with these β-1 AR blockers Gilbert et al 1996;Heilbrunn et al 1989;Michel et al 1988;Sigmund et al 1996;Waagstein et al 1989) is due to their inverse agonism activity. In this context, it is interesting to note that also carvedilol has been found to exert (weak) inverse agonism (Maack et al 2000), but as discussed earlier it did not increase cardiac β-AR density in CHF.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, for bucindolol, several authors have found that it exerts partial intrinsic sympathomimetic activity (ISA) in the human myocardium (Maack et al 2000(Maack et al , 2003Andreka et al 2002). Previous studies had shown, however, that β-AR blockers with intrinsic sympathomimetic activity decrease cardiac β-AR density (Michel et al 1988), and this would explain the lack of cardiac β-AR up-regulation during chronic bucindolol treatment.…”
Section: Effects On β-Adrenoceptor Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…/ON Λ , , lates the samples to be compared. Moreover, the effichange m 2 -adrenoceptor density (2). On the other .…”
Section: Introductionmentioning
confidence: 99%
“…, f , j ι· * ι ο steps needed before PCR amplification cannot be accumarkedly increased due to enhanced coupling of the β 2 -, " t A , , rately monitored. Nevertheless, quantification of an adrenoceptor to effector mechanisms after atenolol treat-·; .…”
Section: Introductionmentioning
confidence: 99%